Marathon shoes vs. track spikes: a crossover pilot study on metabolic demand at different speeds in experienced runners. Issue 1 (2nd January 2023) - Ardigò, Luca Paolo; Buglione, Antonio; Russo, Luca; Cular, Drazen; Esposito, Fabio; Doria, Christian; Padulo, Johnny
ABSTRACT: The aim of this study was to assess the metabolic cost (Cr) with marathon shoes (Adidas Adizero 3 [AA]) vs. track spikes (Nike Zoom Matumbo 3 [NZM]) on track. For this, five experienced runners were randomly assessed (NZM/AA) on a running track at 73% and 85% of best performance speed on 1500-m race. At first, speed (4.39 ± 0.53 m·s −1 ), Crs with AA and NZM resulted 3.63 ± 0.29 and 3.64 ± 0.43 J·kg −1 ·m −1 (+0.3% with NZM, effect size [ES] small and p = 0.951), respectively. Besides, at second speed (5.20 ± 0.18 m·s −1 ), Crs were 4.09 ± 0.28 and 4.07 ± 0.22 J·kg −1 ·m −1 (−0.5% with NZM, ES small and p = 0.919) with AA and NZM, respectively. It resulted in an increased Cr (+12.2%) between s1 and s2 with both shoe conditions (ES large and p = 0.009 and 0.011 with AA and NZM, respectively). There is a pattern yet to be confirmed for track spikes to become more beneficial at higher speeds (when duty factor becomes lower and therefore grip on track is crucial).